Canterbury cross - Ghosh, Ayan (2023)
Dated from around 850 CE, a Saxon-era brooch was discovered in 1867 during excavations at St. Georges Street, Canterbury. Cast in bronze with complex decorations, the design was replicated for a stone cross erected at Canterbury Cathedral. Similar replicas, mounted on fragments of stone from Canterbury Cathedral, are placed in Anglican Cathedrals worldwide. The cross sent to the Diocese of Bombay is embedded in the west wall of St. Thomas Cathedral (at the bottom, between the two plaques as seen in the above figure).